PENERAPAN STRATEGI KOMUNIKASI BADAN PEMBINAAN HUKUM NASIONAL DALAM PROGRAM PENYULUHAN HUKUM BAHAYA NARKOBA DI LEMBAGA PEMASYARAKATAN NARKOTIKA KELAS II A JAKARTA. - S, Muhammad Fajar; Putra, Afdal Makkuraga; Mulyana, Ahmad (Universitas Mercu Buana, 2023)
The adverse effect of drug abuse and drug trafficking is detrimental to people's lives, this has prompted the Ministry of Law and Human Rights and the National Narcotics Agency to focus more on various efforts to prevent the Eradication of Drug Abuse and Illicit Trafficking. Trafficking in Persons (P4GN). Based on data from the Correctional Database System from 9 detention centers and prisons in Jakarta. Jakarta's Class II A Narcotics Prison is currently the prison with the highest number of Narcotics convicts, namely 2,542 people. Based on these problems, the researchers made the mobile law extension program a research. This type of research is descriptive qualitative using communication strategy steps according to Anwar Arifin. The steps of the communication strategy include audience introduction, message preparation, method determination, and media selection. Based on the research results, seen from audience recognition, message preparation, method determination, and media selection, it turns out that the Ministry of Law and Human Rights actually prepared and implemented a communication strategy in the mobile law counseling program.